The Relationship Between Characteristics of Raw Water, Treatment Procedure, Hygiene and Sanitation of The Station, and Bacteriological Characteristics of The Treated Water of The Filling Stations in Manado - Sondakh, Ricky C.; Rattu, Joy A. M.; Kaunang, Wulan P. J. (Jurnal Ilmu dan Teknologi Pangan, 2015)
Refillable bottled water has become an important alternative for the communities in Manado as the water characteristics of residential wells worsen and the local water company, PDAM, is in limited capacity for supplying adequate quantity and quality of water. Many filling stations sell bottled water for about a third of the price of the branded bottled waters, and this prompts the shift of households to these products. As a consequence, there is a proliferation of water filling stations around town. The growth goes along with the increased demand in the community of quality and safe drinking water. Unfortunately, not every filling station exercises proper control on the safety of its product. This is quite concerning because many of the residents of Manado rely on refillable bottled water as their source of drinking water. The objectives of this study were to investigate the relationship between characteristics of raw water, treatment procedure, hygiene and sanitation of the station, and bacteriological characteristics of the treated water of the filling stations in Manado. Water samples were collected from the purposively-selected filling stations spread across 9 sub-districts of Manado. There were in total 35 stations recruited for the study, or about a third of 103 stations in town that had certification of hygiene and sanitation based on the Ministry of Health Regulation No 43 of 2014. Keywords : raw water, treatment procedure, hygiene sanitation of the station, bacteriological characteristics